Hybrid search approach for retrieving Medical and Health Science knowledge from Quran - Safee M.A.M.; Saadan K.; Madihah Mohd Saudi; Sakinah Ali Pitchay; Farida Hazwani Mohd Ridzuan; Nurlida Basir; Nur Fatin Nabila Mohd Rafei Heng (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA